The Influence of School Management in Improving Teacher Performance at Sangkhom Islam Wittya School Sadao, Songkhla Thailand - Adinda Rahmah Rangkuti (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
This paper discusses the influence of school-based management on teacher performance at Sangkhom Islam Wittya School Sadao, Sangkla Thailand. This study aims (1) to determine school-based management at Sangkhom Islam Wittya School Sadao, Sangkla Thailand, (2) to determine teacher performance at Sangkhom Islam Wittya School Sadao, Sangkla Thailand, and (3) to determine the effect of school-based management on performance teacher at Sangkhom Islam Wittya School Sadao, Sangkla Thailand. This research is a quantitative research with an ex post facto research design. Sampling using total sampling technique, the number of samples is equal to the number of population, namely all teachers, totaling 20 teachers. Data obtained through questionnaires and documentation. Furthermore, the research data were analyzed statistically using data management, namely descriptive statistical analysis using the help of the SPSS Version 22 For Windows program. The results of the descriptive study show that school-based management at Sangkhom Islam Wittya School Sadao, Sangkla Thailand is included in the good category with a percentage of 50%, while the mean score is 82.23, and the teacher performance of Sangkhom Islam Wittya School Sadao, Sangkla Thailand is included in the moderate category. good with a percentage of 84%, while the mean score is 54.41. The results of this study indicate that there is a positive influence of school-based management (X) on teacher performance (Y) 0.528 or 52.8%. While the rest is influenced by other factors not examined.